The African American almanac - Narins, Brigham 1962- (Gale virtual reference library, 2008)
Provides a range of historical and current information on African American history, society and culture. Includes coverage of such topics as: Africa and the Black diaspora; film and television; landmarks; national organizations; population; religion; science and technology; and sports.